An investigation of the lexico-grammatical profile of English legal- lay language - Busso, Lucia (Language and Law / Linguagem e Direito, 2022)
The article presents a study on the lexico-grammar of the genre of English legal-lay language (Tiersma 1999), using the English subcorpus of the CorIELLS corpus (Busso forthcoming). The study explores four grammatical constructions (in Goldberg 2006’s Construction Grammar sense): nominalisations heading prepositional phrase attachments, modal verb constructions, participial reduced relative constructions, and passive constructions. Specifically, we use collostructional analysis (Stefanowitsch 2013), followed by a vocabulary analysis using English core vocabulary as a reference (Brezina and Gablasova 2015), and a comparative frequency analysis with corpora of legal language and generaldomain written prose. Results of this first part of the study foreground how legallay language is quantitatively different from both neighbouring genres, suggesting that it might be considered a “blended” genre. We further explore the data in terms of accessibility for speakers, using readability metrics and a survey on English participants. Both methods show that legal-lay language is at an intermediate level of complexity between legal jargon and general-domain prose; however, we further note that readability metrics generally underestimate speakers’ ability to comprehend legal-lay language.